Medan City Development Planning and Challenges and Solutions in City Development Planning - Grace, Shania; Padang, Ratnauli; Saskia, Dwi Putri; Lapian, Inez Adelia; Simanjuntak, Syaloom Lestari; Panggabean, Fitri Yani (PT FORMOSA CENDEKIA GLOBAL, 2025)
The research method used in this study is the literature review method. Research articles collected in this study used manual searches via Google Scholar with the keyword